Se souvenir du féminicide de l’École Polytechnique (1989). Traverser l’espace, recomposer le passé - Vigneault, Louise (RACAR : Revue d'art canadienne / Canadian Art Review, 2022)
This article discusses how certain commemorative artistic creations have allowed the Montreal and Quebec communities to cope with the painful memory of the 1989 anti-feminist mass shooting at École Polytechnique. While feminist interpretations of the tragedy called on the past to reveal its causes, and official readings instead tried to keep the reflections in the present, to dissolve the tensions between the radical positions, certain artistic projects have made it possible to create a third space and to reconcile the past and the present, history and remembrance. Rose-Marie Goulet’s Nef pour quatorze reines (1999), as well as the performative event Une marche, deux parcours : In remembrance of the women of Polytechnique (2019), commemorating the 30th anniversary of the tragedy, are examples testifying to this gesture of remembrance.